Analisis Jawaban Siswa pada Operasi Hitung Campuran Melalui Penerapan Pendekatan Metakognitif-Diskursif - Dekriati Ate (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2018)
[Title: Analysis of Student Answers on Mixed Calculation Operations Through the Implementation of Metacognitive-Discursive Approach] Mixed calculation operations are one of the important topics in mathematics but there are still many students who have difficulty performing mixed calculation operations and are unable to give the right reasons. This research aims to determine the effect of the use of teaching materials that have been designed by didactic mathematicians and have been tested in several schools using a metacognitive-discursive approach. This study was a design study which consisted of 3 phases: the preparation and design phase, the teaching experiment phase, the retrospective analysis phase with the research subjects of 31 students. The results showed that students were able to (1) add and subtract integers, (2) work on a compound calculation operation, and (3) learn the method of saving parentheses from a compound calculation operation. Based on these results it can be concluded that through metacognitive-discursive students can understand mixed calculation operations.